The evaluation and optimization method of major events-driven polluted coastal zone renewal: a case of the polluted coastal zone in the Dalian Barracuda Bay Stadium Area - Gu, Meng; Guo, Qi; Yang, Kexin; Jiang, Bin; Yu, Yang (Frontiers in Environmental Science, 2023)
Coastal zone pollution directly leads to a series of damage to the local ecological, economic, and social benefits. The resilience of polluted coastal zone is a comprehensive challenge that has to deal with the degeneration of ecological services, the decrease in urban livability, and the increase in maintenance costs. Since the current ecological management pays more attention to the relevant technology and investment, it has a limited role in effectively and quickly executing the resilience of polluted coastal zone. Therefore, it is essential to explore a new method for this comprehensive challenge considering ecological, economic, and social aspects. As an implanted production process, major events could act as the engine of regional resilience, since major events have immediate boosting effects on the polluted coastal zones' ecological environments, and further synergistic increase the local social and economic benefits. In this paper, we aim to explore the resilience potential of major events on the polluted coastal zone's social, economic, and ecological aspects. Based on the Nature-based solutions (NbS) theory, a Social-Economical-Ecological Systems Framework (SEESs) of polluted coastal zone resilience driven by major events was established. Driven by hosting the 2023 China Asian Cup, the polluted coastal zone's resilience in Dalian Barracuda Bay Stadium area was studied in this paper. 3 subsystems and 12 indexes were selected as evaluation indexes of polluted coastal zone resilience driven by major events. Further, using the entropy weight method, we constructed an evaluation system of polluted coastal zone resilience benefits driven by major events, then verified the synergistic effect of the major event on the polluted coastal zone's social, economic, and ecological recovery. Moreover, we evaluated the change in the polluted coastal zone's comprehensive scores from 2018 to 2021 under the impact of the 2023 Asian Cup. The spatial and temporal patterns of each subsystem and index were also discussed. Finally, we propose optimization methods of urban polluted coastal zone resilience driven by the major event, and provide solutions to cope with the negative impact of epidemics, strikes, and war along the progress.